Considering Gender and Student Leadership Through the Lens of Intersectionality. Issue 154 (June 2017) - Tillapaugh, Daniel; Mitchell, Donald; Soria, Krista M.
Abstract : This chapter explores the concept of intersectionality and its applicability to student leadership development as well as recommendations on how intersectionality can provide transformative learning for students of all gender identities.